Prevention of pneumococcal infections: Impact of structured medico-pharmaceutical collaborative management to improve vaccination coverage of at-risk patients (OPTIVACC study): Protocol for a multicenter randomized stepped -wedge study - Florent Dubois; Emilie Champiot-Bayard; Bogdan Cireașă; Paul Loubet; Jérôme Vallat; Julie Bonnet; Valérie Jacob; Pauline Puyo; Ioana Pînzar; Sarah Théret; Emmanuelle Dubois; Elisabeth Peus; et al. (Contemporary Clinical Trials Communications)
Background: Streptococcus pneumoniae causes infections especially in patients with immunodeficiency or specific comorbidities. Most could be avoided through pneumococcal vaccination (PV), but PV coverage is only 20 % in France. Many studies assess methods on vaccination coverage improvement, but none evaluates pharmacist-physician collaboration in hospital on PV coverage of inpatients at-risk of invasive pneumococcal disease (IPD). Methods: This study is a multicentric stepped-wedged randomized trial involving 12 units in 9 French hospitals (3 university and 6 local) during 4 periods of 90 days each. Three clusters will be made, each composed randomly of clinical and surgical units from one university hospital and clinical and surgical units of 2 local hospitals. For each period, one unit will have to include 16 non-vaccinated inpatients at risk of IPD. Patients in the control phase will receive usual care. During the interventional phase, the pharmacist will inform the physician on PV necessity, who will report recommendation and prescribe it at discharge. The pharmacist will perform a consultation and send a discharge letter to the patient's community pharmacist. The primary outcome will assess the impact of intervention on PV coverage after 6 months. Secondary outcomes will evaluate vaccines dispensing, uncompleted protocol rate and intervention process. A subgroup analysis between university and local hospitals and clinical and surgical units, respectively will be made. Discussion: This study will assess the impact of medico-pharmaceutical collaboration in hospital on PV coverage in inpatients at risk of IPD. Hospitalization could be a way to promote vaccination and enhance healthcare system performance. Trial registration: Clinicaltrials.gov, NCT05060146. Registered on September 16th, 2021.